O wyznaniu kanarka, dzieciach na kolonii i apologii wszy planowanej przez Janusza Korczaka - Zgrzywa, Agnieszka (My University, 2013)
The point of departure for this article is the memory of moving fragments of Janusz Korczak’s journal from Warsaw ghetto. The author confronts the fragments with Korczak’s earlier texts, such as the short storied about holiday camps for Polish and Jewish children, and the novel "Król Maciuś na bezludnej wyspie" [King Maciuś on a Desert Island]. The image of a canary bird, used in the novel, is confronted with other symbolic stories about this bird, such as the story in Wiesław Myśliwski’s "Pałac" [Palace]. With reference to the image, the article invokes Korczak’s meditations on identity and tolerance, and human ethical and aesthetic choices. The audacity of Korczak’s thoughts and conclusions goes far beyond his time, and seems perfectly fit for ours.
On the Confession of a Canary Bird, Children on a Holiday Camp, and the Apology for Fleas Planned by Janusz Korczak
Keywords: Janusz Korczak; problem of identity; Jews in Poland; rights of children; image of canary bird; memoirs from the ghetto; treatment of animals; Król Maciuś Pierwszy